Transparansi Anggaran Publik Sebagai Kunci Peningkatan Kepercayaan Masyarakat Terhadap Pemerintah Daerah - Hamzah, Mohammad; Surahman, Fajar; Abdurahman, Abdurahman; Saputri, Erina; Basyarahil, Abubakar (Al-Amien Prenduan for Islamic Institute, 2024)
This study aims to analyze the effect of public budget transparency on the level of public trust in the Pamekasan Regency Government. Public budget transparency is defined as adequate openness of information related to the budget preparation, implementation, and evaluation process that can be accessed by the public. Public trust is measured based on public perception of the reliability and accountability of the local government in budget management. Using quantitative methods, this study collected data through a survey with a stratified random sampling technique on 400 respondents selected from various regions in Pamekasan Regency. Data analysis was carried out using simple linear regression to determine the relationship between budget transparency variables and public trust. The results showed that budget transparency had a positive and significant effect on the level of public trust with a regression coefficient of 0.625 and a significance value of 0.000. This finding indicates that the higher the level of budget transparency, the greater the public trust in the local government. This study provides important implications for the development of public policy, especially in increasing budget transparency in order to strengthen public trust.